The role of social entrepreneurship projects in empowering housewives economically and socially - ZEMERLI, Ouarda; NADJEH, Makhlouf (Social Sciences Journal)
This study sought to identify the role of social entrepreneurship in achieving economic and social empowerment for women staying at home, in addition to identifying the concept of social entrepreneurship, its importance, objectives, and sources of funding for social entrepreneurship projects. The most important challenges facing women social entrepreneurs were also addressed, the concept of economic and social empowerment and their importance for women were also addressed. The study relied on two types of secondary sources, represented by collecting bibliography related to the study variables, and primary sources represented by using the interview tool, which included a set of questions related to the study variables and their dimensions, and other questions in order to collect data related to the study problem and its objectives. The study also relied on the faithful analytical approach to achieve the study objectives. Accordingly, the study reached a set of results, the most important of which are: Social entrepreneurship has contributed significantly to empowering many women who are social entrepreneurs and stay-at-home mothers from a social and economic perspective. They have become more self-reliant in obtaining money and improving the financial situation of their families, in addition to their contribution to providing work for some unemployed women, especially university graduat